2001
DOI: 10.1006/jmbi.2000.4335
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 and Sp3 physically interact and co-operate with GABP for the activation of the utrophin promoter

Abstract: The utrophin gene codes for a large cytoskeletal protein closely related to dystrophin which, in the absence of dystrophin, can functionally substitute it. Utrophin is transcribed by two independently regulated promoters about 50 kb apart. The upstream promoter is TATA-less and contains a functional GABP binding site which, in muscle, restricts the promoter activity to post-synaptic nuclei. Transient transfections analysis of mutant promoters in rhabdomyosarcoma cells showed that the upstream promoter contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 66 publications
(98 reference statements)
3
45
0
Order By: Relevance
“…S10). SP1, YY1, and GABPA have been previously described as interacting partners (Galvagni et al 2001;Rosmarin et al 2004), and these pathway enrichments are consistent with previous studies implicating GABPA in controlling stem cell maintenance and differentiation (Yu et al 2016). …”
Section: Dap Binding Recapitulates Known Liver Expression Programssupporting
confidence: 90%
“…S10). SP1, YY1, and GABPA have been previously described as interacting partners (Galvagni et al 2001;Rosmarin et al 2004), and these pathway enrichments are consistent with previous studies implicating GABPA in controlling stem cell maintenance and differentiation (Yu et al 2016). …”
Section: Dap Binding Recapitulates Known Liver Expression Programssupporting
confidence: 90%
“…When comparing our model systems, higher levels of GABP mRNA are associated with higher levels of steady state TSPO mRNA. GABP is also a target of c-Raf and JNK (49), and it physically interacts and cooperates with Sp1 and Sp3 for the activation of at least one promoter (50). Interestingly, absence of Ets1 mRNA is also associated with high levels of TSPO mRNA, an observation that is corroborated by the fact that induced downregulation of Ets1 in NIH/3T3 cells results in increased TSPO mRNA.…”
Section: Discussionmentioning
confidence: 94%
“…We and others (Gramolini et al, 1999a;Khurana et al, 1999) have shown that the nerve-derived growth factor heregulin (HRG) causes a N-box-mediated increase in utrophin-A promoter activity via extracellular signal-regulated kinase-dependent activation of the Ets-related transcription factor complex GABP␣/␤, in a manner similar to that noted in the nACHR␦ and nACHR subunit promoters (Falls et al, 1993;Koike et al, 1995;Sapru et al, 1998; This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E06 -12-1069) on May 16, 2007. 1998). Additionally, SP1 (Galvagni et al, 2001;Gyrd-Hansen et al, 2002), NFATc1/calcineurin (Chakkalakal et al, 2003;Chakkalakal et al, 2004), and myogenic factors (Gramolini and Jasmin, 1999;Perkins et al, 2001) can also activate the utrophin-A promoter. Recently, the 5Ј-untranslated region of utrophin-A promoter has been shown to be important for regulation of utrophin protein levels during regeneration as well (Miura et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SP1 (Galvagni et al, 2001;Gyrd-Hansen et al, 2002), NFATc1/calcineurin (Chakkalakal et al, 2003;Chakkalakal et al, 2004), and myogenic factors (Gramolini and Jasmin, 1999;Perkins et al, 2001) can also activate the utrophin-A promoter. Recently, the 5Ј-untranslated region of utrophin-A promoter has been shown to be important for regulation of utrophin protein levels during regeneration as well (Miura et al, 2005).…”
mentioning
confidence: 99%